2006
DOI: 10.4049/jimmunol.176.8.4716
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ Acts on T Cells to Induce NK Cell Mobilization and Accumulation in Target Organs

Abstract: The mechanism(s) that regulates NK cell mobilization and the significance of this process to NK cell activity are unknown. After Con A-induced hepatitis, NK cells are mobilized from the spleen and bone marrow into the periphery in an IFN-γ-dependent fashion. Intraperitoneal administration of IFN-γ stimulates the mobilization of NK cells into the circulation, but not their cell death or proliferation. Increased number of circulating NK cells was coupled with their accumulation in the peritoneum, liver, and tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 37 publications
5
65
0
2
Order By: Relevance
“…The percentage of NK cells in the spleen decreased from 3.75% in noninfected animals to 1.96% in infected animals after 4 dpi and from 3.6% to 1% after 7 dpi (Figure 1A,B), suggesting that NK cells may have migrated away. This is consistent with other T. gondii infection models12, 23 and with the idea that inflammation induces mobilization of NK cells from storage depots in the spleen to the blood and inflamed tissue 24. However, after 4 or 7 dpi, the percentage of NK cells was similar in the brain of noninfected and infected animals (Figure 1B).…”
Section: Resultssupporting
confidence: 91%
“…The percentage of NK cells in the spleen decreased from 3.75% in noninfected animals to 1.96% in infected animals after 4 dpi and from 3.6% to 1% after 7 dpi (Figure 1A,B), suggesting that NK cells may have migrated away. This is consistent with other T. gondii infection models12, 23 and with the idea that inflammation induces mobilization of NK cells from storage depots in the spleen to the blood and inflamed tissue 24. However, after 4 or 7 dpi, the percentage of NK cells was similar in the brain of noninfected and infected animals (Figure 1B).…”
Section: Resultssupporting
confidence: 91%
“…Recent reports (35,36) suggested that CxCR3, in addition to its critical role in recruiting T cell during allograft rejection, is also important in regulating NK cell mobilization under normal and pathogenic conditions (37). CxCR3 is also essential for NK-dependent antitumor responses in vivo (38).…”
Section: Discussionmentioning
confidence: 99%
“…It is still plausible that CXCL9 and/or CXCL10 could affect the activation of other cell subsets, including NK cells, by enhancing cytolytic activity as a result of augmented IFN-␥ production or enhanced proliferation, ultimately leading to increased antiviral activity (28,54,55). Conversely, CXCL9 and/or CXCL10 could play a role in limiting cytokine-mediated liver immunopathology.…”
Section: Discussionmentioning
confidence: 99%